2011
DOI: 10.1002/glia.21183
|View full text |Cite
|
Sign up to set email alerts
|

Role of Müller cells in cone mosaic rearrangement in a rat model of retinitis pigmentosa

Abstract: Retinitis pigmentosa (RP) is a type of inherited retinal degenerative disease, which leads to blindness. The primary pathological event of this disease is the death of rods because of genetic mutations. The S334ter-line-3 rat is a transgenic model developed to express a rhodopsin mutation similar to that found in RP. In this study, the rod's death triggered are organization of the cone mosaic into an orderly array of rings. Four observations were relevant to understand this reorganization. First, rods died in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
68
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(74 citation statements)
references
References 53 publications
6
68
0
Order By: Relevance
“…Strettoi and co-workers proposed that neurons in retinal degeneration undergo dendritic pruning and later, sprouting due to loss of their afferent synapses (Strettoi and Pignatelli, 2000;Strettoi et al, 2002Strettoi et al, , 2003. This is supported by Lee et al (2011), who showed Müller cell processes remodel to match photoreceptor rearrangement in a rat model for retinitis pigmentosa. Altered glutamate signaling during retinal degeneration may also play an indirect role.…”
Section: Anatomical Remodelingmentioning
confidence: 85%
“…Strettoi and co-workers proposed that neurons in retinal degeneration undergo dendritic pruning and later, sprouting due to loss of their afferent synapses (Strettoi and Pignatelli, 2000;Strettoi et al, 2002Strettoi et al, , 2003. This is supported by Lee et al (2011), who showed Müller cell processes remodel to match photoreceptor rearrangement in a rat model for retinitis pigmentosa. Altered glutamate signaling during retinal degeneration may also play an indirect role.…”
Section: Anatomical Remodelingmentioning
confidence: 85%
“…5,9 However, it is still unclear why the cone mosaic is reorganized into rings after photoreceptor loss. It has been suggested that cone rings could be the result of cone migration through processes of Müller cells 81 ; whereas other authors have proposed that it is due to cone death, 68 these studies indicated that rods die in the ''center of the rings'' and photoreceptor (cones and rods) loss expands outward, 27,68 suggesting an interdependence between neighboring photoreceptors. 82,83 Thus, it is likely that rings of cone degeneration could be the result of both cone death and migration.…”
Section: Taurine Depletion Increases Retinal Degenerationmentioning
confidence: 88%
“…After preliminary testing, 25 ug/ml was used throughout this study. The developmental stage for the injection of SB-3CT was either P15, when there was peak rod death [52] and formation of dying rod clusters [31, 32], or P40, when cone rings were observed throughout the retina [36]. One eye was injected with SB-3CT and the other eye was injected with PBS with 0.05–0.1% DMSO for comparison for each animal.…”
Section: Methodsmentioning
confidence: 99%